Bullying and Quality of Life in Pediatric Alopecia Areata - Christensen, Theresa (Skin Appendage Disord, 2017)
Alopecia areata (AA) is a clinically heterogeneous disease that is characterized by nonscarring hair loss, nail changes, and increased risk of other autoimmune disease. During clinical visits, children with AA often report bullying. We report survey results that highlight the prevalence of bullying and surrounding emotional impact of AA in pediatric patients. We found that bullying was common overall and additional psychological impact, including impairment of social and home life, was even more common. Children of all ages experienced bullying. Boys reported increased physical bullying. Interestingly, those with more severe disease and longer duration of disease experienced less bullying than those with less severe disease.